Pengaruh Leverage, Ukuran Perusahaan dan Profitabilitas Terhadap Ketepatan Waktu Pelaporan Keuangan - Maulidayanti, Disya (Journal of Economics Review (JOER), 2024)
This research aims to analyze the influence of leverage, company size, and profitability on the timeliness of financial reporting. The population of this research is all banking companies listed on the Indonesia Stock Exchange (BEI) in 2018-2022. The sampling technique used a purposive sampling to obtain a sample of 29 companies, and the observation population was 145. The data analysis technique used logistic regression and was processed using Eviews 12. The data analysis shows that company size influences the timeliness of financial reporting. Meanwhile, the leverage and profitability variables do not affect the timeliness of financial reporting in banking companies listed on the Indonesian Stock Exchange in 2018-2022